Effects of heat and acid stress on bacterial populations of beef, and on susceptible and multi-antimicrobial resistant Salmonella isolated from beef - Bacon, Richard Todd, author; Sofos, John N., advisor; Smith, Gary C., committee member; Belk, Keith E., committee member; Hyatt, Doreene R., committee member (Colorado State University. Libraries, 2002)
Studies were conducted to serve as initial investigations evaluating antimicrobial efficacies of decontamination treatments applied to beef carcass tissue following chilling, prevalence of susceptible and antimicrobial resistant Salmonella on beef animal hides and carcasses, and whether antimicrobial resistance provided cross-protection against low-pH or heat stress. Results of studies evaluating methods to improve microbiological quality of chilled beef carcasses, subprimal cuts, and fabrication table surfaces, suggested reduced antimicrobial efficacy (≤ 1 log CFU/100 cm2 reduction) of steam-vacuuming and lactic acid solution rinsing when applied during beef carcass fabrication. Study results also supported concerns regarding increased antimicrobial resistance among foodborne bacterial populations, as data indicated that 10.7% of beef animal hide samples contained Salmonella resistant to at least one of thirteen antimicrobials screened. Salmonella isolated from beef animal hides and carcasses were used to evaluate acid and heat tolerance among susceptible and multi-antimicrobial resistant strains. Under the conditions of these studies, results comparing the stress resistance between susceptible and multi-antimicrobial resistant Salmonella, following preparation under acid tolerance-inducing and noninducing conditions, suggested that previous induction of a stationary-phase acid tolerance response afforded increased acid and heat resistance. However, the ability of Salmonella to avoid or repair damage associated with low-pH or thermal stress appeared to be independent of antimicrobial susceptibility.
Keywords: microbiology